2017
DOI: 10.3906/sag-1611-90
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and analysis of invasive fungal infections in patients withhematological malignancies: a single-center real-life experience

Abstract: Background/aim: Invasive fungal infection (IFI) causes morbidity and mortality among patients with hematological malignancies. We evaluated the incidence and treatment characteristics of IFIs between October 2012 and December 2013. Materials and methods:Patients who received chemotherapy or stem cell transplantation were retrospectively evaluated. Fungal infections were classified according to EORTC criteria.Results: Prophylaxis and antifungal therapy were given in 30.5% and 23.6% of 522 chemotherapy courses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our results indicated that the rate of systemic AFT, the incidence of probable/proven IFI and IFI-attributable mortality were 13%, 5% and 20%, respectively, which were comparable with the findings reported from other studies in this particular setting [1–4,24,25]. The SEIFEM-2004 study reported an incidence of IFI of 4.6%, and IFI-attributable mortality rate was 39%, higher than ours [1].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results indicated that the rate of systemic AFT, the incidence of probable/proven IFI and IFI-attributable mortality were 13%, 5% and 20%, respectively, which were comparable with the findings reported from other studies in this particular setting [1–4,24,25]. The SEIFEM-2004 study reported an incidence of IFI of 4.6%, and IFI-attributable mortality rate was 39%, higher than ours [1].…”
Section: Discussionsupporting
confidence: 90%
“…The SEIFEM-2004 study reported an incidence of IFI of 4.6%, and IFI-attributable mortality rate was 39%, higher than ours [1]. In two recent studies from Turkish and Taiwan groups incidence of probable/proven IFI was 6.7% and 5.6% and IFI-attributable mortality was 14.2% and 5.9% respectively [24,25]. In the Hema-e-Chart registry 14% of patients died within 12 weeks after the start of antifungal therapy; IFI-attributable mortality was 30.4% and 17.3% in yeast and proven/probable mold infections, respectively [4].…”
Section: Discussionmentioning
confidence: 59%
“…There are currently no epidemiological data on nation‐wide burden of fungal infections in Turkey, a country located at the crossroads between Eastern Europe and Western Asia with prominent geographical and socioeconomic diversity. Several studies have examined the epidemiology of fungal infections and antifungal utilisation in Turkey, but most were local, single‐centre or regional and focused on individual infections in specific populations. For instance, the epidemiology of candidiasis was evaluated retrospectively at the Hacettepe University Hospital in Ankara between January 2001 and December 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A single‐centre study between October 2012 and December 2013 at Ege University in İzmir showed that incidence of proven and probable invasive fungal infections (IFIs) was 6.7% in those with haematological disease. Prophylaxis and antifungal therapy were given only in 30.5% and 23.6% of 522 chemotherapy episodes, respectively . Another study reported the epidemiological trends in antifungal treatment on the national level; 408 patients and 505 episodes of invasive fungal infections was recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of IFI was high at 26.5% with an incidence of Proven/probable IFI being 8.25%. A metaanalysis involving 49 published studies suggested a IA risk of 4% with the use of anti-fungal prophylaxis but real world data report incidences ranging from 1.7 to 12% despite the use of antifungal prophylaxis [19][20][21]. The actual incidence in our study may have been even higher since few centres did not have access to the use of galactomannan antigen during the period of this study and therefore all IFIs from those centres were reported as possible IFI.…”
Section: Discussionmentioning
confidence: 66%